SAT0113 Obesity and metabolic syndrome influence on n-terminal pro-brain natriuretic peptide levels in rheumatoid arthritis patients. (15th June 2017) - Kondratyeva, L; Popkova, T; Kirillova, I; Novikova, D; Novikov, A; Alexandrova, E; Nasonov, E
Abstract : Background: N-terminal pro-brain natriuretic peptide (NT-proBNP) is a recognized myocardial injure marker, a known predictor of heart failure and cardiovascular death. Rheumatoid arthritis (RA) patients (pts) were shown to have higher than in general population NT-proBNP concentrations, positively correlating with IL-6 levels. Adipose tissue is considered be one of the sources of this pro-inflammatory cytokine. But on the other hand, metabolic syndrome (MS) and obesity, which also occur in RA pts, are usually associated with lower NT-proBNP levels in general population. Objectives: To find out whether overweight/obesity or MS may modify NT-proBNP levels in RA pts. Methods: A total of 68 early RA pts (72% females, 28% males) was enrolled in the study. Mean disease duration was 6 [4;8] months, and RA activity using DAS28 calculator was 5, 6 [5, 1;6, 4] scores. The majority of pts had positive RF (87%) and ACPA (88%). All pts were glucocorticoids and disease-modifying antirheumatic drugs - naïve prior to inclusion. The overweight/obesity was determined by WHO criteria in patients with body mass index (BMI) ≥25 kg/m 2 . National Cholesterol Education Program/Adult Treatment Panel III criteria were used to confirm MS. Serum levels of NT-proBNP (pg/mL) were measured using electrochemiluminescence test Elecsys proBNP II (Roche Diagnostics, Switzerland). NT-proBNP levels >125, 0 pg/mL were considered as elevated. Results: Overweight and obesity were established in 54, 4% RA pts. Overweight/obese RA pts were older than pts with normal BMI (57 [53;61] years vs 48 [34;61] years, p =0, 02), had higher DAS28 scores (5, 85 [5, 20;6, 57] vs 5, 28 [4, 76;5, 69], p <0, 01), higher CRP (38, 8 [14, 3; 47, 9] mg/L vs 12, 8 [2, 2;28, 8] mg/L, p <0, 01). Elevated NT-proBNP concentrations were found in 62, 2% overweight/obese pts vs 29, 0% pts with normal weight ( p <0, 01), median NT-proBNP concentrations were 153, 4 [87, 3;236, 9] pg/mL vs 75, 2 [40, 2;147, 4] pg/mL, respectively ( p =0, 02). MS was established in 62, 2% pts with BMI ≥25kg/m 2 and in 25, 8% pts with BMI<25kg/m 2 ( p <0, 01). Median NT-proBNP concentrations did not vary significantly in pts with and without MS, whether they were overweight/obese ( p =0, 75), or had normal BMI ( p =0, 27). Although higher rates of elevated NT-proBNP concentrations were documented in pts with MS (61, 3% vs 35, 1%, p=0, 03). NT-proBNP levels positively correlated with waist circumference (r=0, 33, p <0, 01), ESR (r=0, 25, p =0, 04), and CRP (r=0, 3, p =0, 01). Conclusions: Overweight and obesity in RA pts were associated with increased NT-proBNP levels. Abdominal obesity was identified as the only MS component, influencing NT-proBNP levels, presumably via up-regulation of the inflammatory process. Disclosure of Interest: None declared